Shock absorber i.e. crash box, for protecting hip and/or legs of pedestrian during collision of motor vehicle with pedestrian, has air passage to pass air toward heat exchanger, and air flow regulating unit to regulate air flow in passage - LANARD JEAN LOUIS; VAN HOUTEGHEM GAEL; GUINEHUT SEBASTIEN (2010)
The absorber has an air passage (13) for passing air toward a heat exchanger e.g. condenser or radiator, where the absorber is made of plastic material. The passage is a channel traversing a deformable block (12). An air flow regulating unit regulates flow of air in the passage, where the passage has a constant and non-adjustable section. The regulating unit comprises a movable flap (27) that is placed in the passage and fixed on a rotary axis (28). The deformable block is deformed under action of shock. L'invention concerne un absorbeur de chocs de véhicule automobile comprenant au moins un passage d'air (13) vers un échangeur de chaleur et des moyens (27) de réglage du débit d'air. Grâce à l'invention, il est possible de réguler l'air admis dans l'échangeur de chaleur sans nuire à la compacité de l'ensemble.